Papua New Guinea food price bulletin: July 2024 - International Food Policy Research Institute; Hayoge, Glen; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2024)
This bulletin provides an overview of select food prices during the second quarter of 2024, from April to June. During this quarter, two rounds of data were collected per month across all markets, except for Goroka in April and Lae in May, where only one round of data was collected. The prices presented here are the monthly averages. The graphs in this bulletin show price changes within the second quarter and compare second quarter prices with the first quarter of 2024, between January and March. To access the complete food price dataset, please download it from our website.